2003
DOI: 10.1046/j.1365-2222.2003.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial and environmental determinants for wheezing and asthma in a case‐control study of school children in Palestine

Abstract: Our study confirmed that familial 'atopic' diseases are significant predictors of childhood asthma in Palestinian children. Moreover, indoor environment such as presence of cats and domestic moulds also appear to play a role. Our findings are consistent with studies in Canada, New Zealand, Estonia and Sweden, and show promise to explore further gene-environment interaction in the genesis of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 78 publications
(117 reference statements)
1
21
1
Order By: Relevance
“…Previous studies have found maternal asthma, 38 paternal asthma, 39 or both to be a significant risk factor for the development of asthma and wheezing in children. 40,41 In our study only paternal asthma was significant.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found maternal asthma, 38 paternal asthma, 39 or both to be a significant risk factor for the development of asthma and wheezing in children. 40,41 In our study only paternal asthma was significant.…”
Section: Discussionmentioning
confidence: 96%
“…Nested in this study, we carried out a case-control study to explore the as- sociations between a number of traditional risk factors and asthma (12). We found, among other things, that a positive skin prick test (SPT) against house dust mites and cockroaches was positively associated with wheeze and asthma; the presence of specific immunoglobulin (Ig)E against house dust mites and cat allergens was associated with an increased risk for wheeze.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, furry pets have been associated with rhinitis and wheezing, and these animals can also provoke allergic reactions. 5 Some surveys have found that wheezy children were more likely to own a furry pet than nonwheezy children.…”
mentioning
confidence: 99%
“…5 Some surveys have found that wheezy children were more likely to own a furry pet than nonwheezy children. 3,4 However, other surveys have failed to show these associations. 3,6,7 Therefore, it remains unclear whether exposure to pets including hamsters is related to allergic symptoms.…”
mentioning
confidence: 99%